Perspektywa jako narzędzie komunikacji. Fotografie mody autorstwa Jeanloupa Sieffa - Piszczałka, Anna (Załącznik Kulturoznawczy, 2019)
The aim of the article is to confirm the assumption that perspective is one of the tools that build a photographic act of communication. It has been observed that the perspective allows to obtain the illusion of the third dimension on the two-dimensional surface of the photograph but also creates multiple systems of meaning and even becomes a symbolic form. The focus was on the works of Jeanloupe Sieff, a photographer who used a perspective tool in an innovative way that allowed him to create both realistic, ‘superficial’ presentations and surrealistic, ‘deep’ meaning contexts.